ON THE ISSUE OF THE DEVELOPMENT OF LEADERSHIP QUALITIES OF STUDENTS OF PEDAGOGICAL SPECIALTIES - Ualieva, Nazym; Murzalinova, Alma; Жунусова, Асемгуль; Kuzenbaeva, Aigul; Zhanpeisova, Anara (Pedagogy and Psychology, 2023)
The problem of developing the leadership qualities of future teachers is considered in the article, and the demand for educational leadership for the motivated promotion of innovations by teachers is also substantiated. The team of authors indicated the following components of the organizational system for the formation of leadership qualities: motivational, meaningful, operational, and productive. The diagnostic results are reflected using questionnaire methods (diagnosis of the methodology of E.S. Fedorov and O.V. Yeremin “I am a leader”, the questionnaire "Leadership qualities are a component of my profession"). The content of training students for the development of relevant leadership competencies is presented, the characteristics for the development of appropriate educational and methodological support in the discipline “Introduction to Pedagogical Activity”, necessary for organizing the phenomenon under study, are considered. Developing opportunities and ways to reveal leadership behavior aimed at the motivational-value sphere of activity, self-education and self-development, components of professional competence of students of the specialties 6В01301 “Pedagogy and Methods of Primary Education”, 6В01201 “Preschool Education and upbringing” are determined.